p. K832R and p. T991T polymorphisms' analysis in Cuban patients with clinical diagnosis of Wilson's disease - yulia Clark Feoktistova; Caridad Ruenes Domech; Elsa F. García Bacallao; Hilda Roblejo Balbuena; Zoe Robaina Jiménez; Estela Morales Peralta (Universidad de Ciencias Médicas de La Habana, 2017)
Introduction: Wilson's disease is characterized by accumulation of copper in the liver, brain and cornea. It is transmitted with an autosomal recessive inherited disorder. The molecular causes are mutations in the ATP7B gene. It has been reported in the literature more than 139polymorphisms of the ATP7B gene. Objective: Identify the conformational changes in exons 10 and 13 and detect the polymorphisms p.K832R and p.T991T in the ATP7B gene in Cuban patients with clinical diagnosis of Wilson's disease. Material and Methods: Was performed a descriptive study including 27 patients with Wilson's disease ranging in the time from 2012 to 2013. Were applied the polymerase chain reaction to amplify the fragment of interest and the Conformation Polymorphism Single-Chain procedures in the exon 10 and 13 of the ATP7B gene. The p. K832R and p. T991T polymorphisms were detected by sequencing this fragment. Results: Three different conformational changes were identified: (a, b and c) in exon 10 and (a and b) in exon 13 of the ATP7B gene. The allelic frequency of polymorphisms p. K832R and p. T991T in 27 Cuban patients with clinical diagnosis of Wilson's disease is 35.2% and 5.6%, respectively. Conclusions: It is the first time in Cuba that a combination of the polymorphisms p. K832R and p. T991T were identified which will allow to make possible molecular studies by indirect methods. Keywords: Wilson's disease, p. K832R polymorphism, p. T991T polymorphism, SSCP, sequencing, ATP7B gene.